Radon Pollution in Romania – A Serious and Inssuficiently Known Problem - Dorobăț, Magdalin Leonard Dorobăț; Turtureanu, Anca; Popa, Ionuț; Dobrescu, Codruța Mihaela (Journal of Danubian Studies and Research, 2025)
Abstract: Radon is a natural, colorless, odorless and tasteless radioactive gas that comes from the disintegration of uranium in soil and rocks. Although it is naturally present in the environment, high concentrations of radon in inhabited habitats, such as homes, schools, workplaces, can represent a major risk to the health of the population. In Romania, radon pollution is a serious environmental problem, but insufficiently known and often ignored in public health policies. At the European level, some EU or non-EU countries, such as the United Kingdom, are more advanced in studying this phenomenon and in regulations to mitigate the consequences of pollution with this inert gas. Romania is one of the European countries with high radon levels, due to the geological characteristics of the geological substratum or soil. High-risk regions include mountainous and submountainous areas, as well as areas with uranium-rich soils, such as some areas in the counties of Suceava, Bihor, Caraș-Severin and others. However, monitoring of radon concentration in homes and public buildings is still sporadic, and awareness among the population is very low. This needs to be addressed through environmental and health policies at the national level. Radon becomes dangerous when it accumulates inside buildings, especially in poorly ventilated spaces. Prolonged inhalation of this gas can cause serious conditions, especially lung cancer. It has been found that this problem is not only national, but also global, for example, approximately one fifth, perhaps even more, of lung cancers worldwide are caused by radon pollution of the inhabited habitat. In fact, the World Health Organization (WHO) classifies radon as the second leading risk factor for lung cancer, after smoking. Estimates show that hundreds of deaths annually in Romania can be correlated with radon exposure. Although European legislation (through Directive 2013/59/EURATOM) obliges member states to take concrete measures to reduce the population’s exposure to radon, the application of these regulations in Romania is delayed. Although there are initiatives to measure and map radon levels (such as the “RomRad” project), the lack of funds, specialists and political interest is holding back progress. Compared to other European countries, Romania is at a much more backward stage in terms of monitoring this parameter at national level. For now, measurements and monitoring have started in the western part of Romania and have expanded very slowly to the other regions. National authorities have the obligation to implement a coherent environmental policy in this area, but together with public health policies, finding solutions and regulations that should be legislated and applied in the construction sector. First of all, however, it is very important to raise awareness of the problem, in order to find solutions to a problem, it must first be recognized that the problem exists! Some solutions are more accessible, simpler, such as implementing ventilation habits, natural ventilation of the inhabited habitat, while other solutions are more expensive and complicated, requiring financing. The first step, however, is to inform the population and the authorities about the real danger posed by radon. The second step would be to develop a coherent and sustained national strategy to identify problem areas and then find a set of solutions to reduce radon pollution. Radon pollution will likely continue to silently affect the health of Romanians for a long time, remaining one of the most underestimated environmental threats in the country, but this is true not only for Romania, but also for many other countries in Europe and on other continents. Kewords: idoor radon level, reducing radon poluttion; danger awareness